2003
DOI: 10.1172/jci200317215
|View full text |Cite
|
Sign up to set email alerts
|

Role of RANK ligand in mediating increased bone resorption in early postmenopausal women

Abstract: Studies in rodents have implicated various cytokines as paracrine mediators of increased osteoclastogenesis during estrogen deficiency, but increases in RANKL, the final effector of osteoclastogenesis, have not been demonstrated. Thus, we isolated bone marrow mononuclear cells expressing RANKL on their surfaces by two-color flow cytometry using FITC-conjugated osteoprotegerin-Fc (OPG-Fc-FITC) as a probe. The cells were characterized as preosteoblastic marrow stromal cells (MSCs), T lymphocytes, or B lymphocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
108
1
4

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 625 publications
(114 citation statements)
references
References 49 publications
1
108
1
4
Order By: Relevance
“…The pivotal role that Ikeda et al document for c-Jun in osteoclast formation is in keeping with the fact that the anti-bone resorptive effects of estrogen are substantially mediated by c-Jun repression (20). Given that RANKL expression is also enhanced in estrogen-deficient women (21), RANKL → TRAF6 → MAPK kinase 7 (MKK7) → JNK1 → Jun → NFAT signaling is likely pivotal to the pathogenesis of postmenopausal osteoporosis, and inhibition of any of the components will theoretically arrest accelerated bone resorption ( Figure 1). The therapeutic challenge is how to specifically target these intracellular signaling molecules in osteoclasts.…”
Section: Nfat and Ap-1 In 2002 Takayanagi Et Al Identified Nfat2mentioning
confidence: 84%
“…The pivotal role that Ikeda et al document for c-Jun in osteoclast formation is in keeping with the fact that the anti-bone resorptive effects of estrogen are substantially mediated by c-Jun repression (20). Given that RANKL expression is also enhanced in estrogen-deficient women (21), RANKL → TRAF6 → MAPK kinase 7 (MKK7) → JNK1 → Jun → NFAT signaling is likely pivotal to the pathogenesis of postmenopausal osteoporosis, and inhibition of any of the components will theoretically arrest accelerated bone resorption ( Figure 1). The therapeutic challenge is how to specifically target these intracellular signaling molecules in osteoclasts.…”
Section: Nfat and Ap-1 In 2002 Takayanagi Et Al Identified Nfat2mentioning
confidence: 84%
“…Recently a monoclonal antibody against RANKL was shown to produce prolonged inhibition of bone resorption in postmenopausal women (47). It was also shown that RANKL levels were increased on the surface of bone marrow cells from early postmenopausal women who are estrogen deficient (48). However, it has been difficult to demonstrate a role for OPG deficiency in the pathogenesis of osteoporosis, since OPG levels are not consistently altered.…”
Section: Receptor Activator Of Nf-κb Its Ligand and Osteoprotegerinmentioning
confidence: 99%
“…The mechanisms through which estrogen deficiency stimulates bone resorption remain controversial. Direct effects on osteoclasts (2)(3)(4), upregulation of the osteoclast-inductive cytokine RANK ligand (RANKL) (5), or downregulation of its decoy receptor osteoprotegerin in osteoblasts (6) have been reported. In addition, several inflammatory cytokines have been implicated: estrogen has been reported to suppress expression of TNF-α, IL-1, and IL-6 in osteoclast-supportive bone marrow stromal cells, monocytes, and lymphocytes (see refs.…”
Section: Introductionmentioning
confidence: 99%